The role of ultrasonographic synovial assessment in rheumatoid arthritis patients with concomitant fibromyalgia - Musa Polat; Abdulvahap Kahveci; Duygu Tecer; Zafer Günendi; Feride Göğüş (Archives of Rheumatology, 2023)
Objectives: This study aimed to compare the prevalence and musculoskeletal ultrasonography (US) findings of rheumatoid arthritis (RA) patients with concomitant fibromyalgia (FM) according to the 1990 American College of Rheumatology (ACR) FM classification criteria or the 2016 ACR FM diagnostic criteria. Patients and methods: This cross-sectional study included 63 patients (17 males, 46 females; mean age: 48.2±7.1 years; range, 18 to 62 years) with RA. Medical history and laboratory data were obtained from electronic records. Clinical examination, composite disease activity measures, functional status, and the German 7-joint ultrasound score were assessed to evaluate disease activity and synovial inflammation. The patients were divided into three groups: patients who met only the 2016 ACR criteria, patients who met only the 1990 ACR criteria, and patients who met both criteria. Results: In patients with RA, concomitant FM prevalence was 34.9% according to the 2016 ACR FM diagnostic criteria versus 23.8% according to the 1990 ACR FM classification criteria. Rheumatoid arthritis patients with FM had high tender joint count and disease activity scores, while musculoskeletal US findings were similar. Patients who met only the 2016 ACR FM diagnostic criteria had significantly higher gray-scale US and power Doppler US synovitis scores than patients who satisfied only ACR 1990 FM classification criteria (p=0.03 and p=0.02, respectively). Conclusion: Synovial inflammation is a prominent sign in RA patients diagnosed with FM according to the 2016 ACR FM diagnostic criteria. The higher disease activity seen in the presence of FM in RA patients is associated with FM rather than synovitis.